(untitled) (INNOVATIVE ECONOMY, 2024)
Svynous I.V., Turzhanskyi V.A., Khoma D.M. METHODICAL APPROACHES TO KEEPING RECORDS OF PAYROLL CALCULATIONS ACCORDING TO INTERNATIONAL STANDARDS OF FINANCIAL REPORTING Purpose. The aim of the article is to offer practical recommendations on the use of international financial reporting standards in the accounting for wages in Ukraine based on the generalization of the experience of countries around the world that use these standards of financial reporting in the accounting process. Methodology of research. The theoretical and methodological basis of the research is scientific concepts, theoretical developments of leading scientists on the issues of payroll accounting, its analysis, control and budgeting. General scientific and special research methods were used to achieve the set goal: observation, analysis and synthesis, a comprehensive approach – in the generalization and improvement of the main theoretical provisions and methodical principles of accounting for labour payments; system approach – when studying the features of the payroll management system and determining the place of integrated accounting in it. Findings. An analysis of the use of international standards of financial reporting in the implementation of salary accounting was carried out. It was proven that the IFRS system, unlike the PSBO system, does not operate with the concept of “payments related to wages”. International standards use another category – “employee benefits”. Differences between these indicators are observed when analysing the elemental classification of expenditures. Originality. The root causes of the differences between domestic accounting standards and IFRS when accounting for the wages of employees of economic entities are substantiated. It was established that the problem of standardization for the Ukrainian economy is that all international financial reporting standards are developed for the conditions of a developed market economy, so most of them are not acceptable for our country in their entirety. Practical value. Entities of entrepreneurial activity that, in accordance with current domestic legislation, keep records based on IFRS, have the opportunity to implement the process of adaptation of keeping records of wage calculations, taking into account the peculiarities of economic relations and legal acts that regulate the calculation and payment of wages to hired workers. Key words: international standards of financial reporting, national accounting standards, salary, monetary reward, enterprise.